Cultivating Sustainable Tourism Technopreneurs: A Serial Mediation Analysis of AI-Augmented Ideation and Business Model Innovation in Vocational Education - Arifin, Asyam Faris Khoirul; Ibrahim, Hammam Rizky; Mubarok, Muadzin Nur; Setiyani, Shinta; Sakova, Megha (Integrasi Sains Media, 2026)
The rapid smartization of the tourism industry, driven by generative artificial intelligence (AI), has redefined the competencies required for future technopreneurs, yet the mechanism through which digital preparedness translates into sustainable outcomes remains under-researched in vocational contexts. This study proposes and tests a serial mediation model examining the interplay between digital foundations (literacy and self-efficacy), AI-augmented Ideation, ethical awareness, and sustainable business model innovation (SBMI). Utilizing a quantitative approach, data were collected from 200 vocational tourism students in Indonesia and analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that digital literacy and AI self-efficacy significantly drive technopreneurial readiness only when sequentially mediated by creative Ideation and strategic filters. Specifically, the path from AI-augmented Ideation to technopreneurship is optimized through the serial role of Ethical AI Awareness and SBMI, illustrating that technological efficiency must be balanced with normative responsibility and value reconfiguration. These findings have critical implications for vocational higher education, suggesting that curricula must move beyond technical training to foster the ethical and strategic capabilities necessary for a resilient, green hospitality ecosystem.